Occupational chemical safety and management: A case study to identify best practices for sustainable advancement of Bangladesh - Amit Hasan Anik; Mohammad Toha; Shafi M Tareq (Elsevier, 2024)
Bangladesh has experienced numerous tragedies and casualties in the chemical industry, resulting in unparalleled losses in terms of human, social, and economic adversity, primarily attributed to the absence of effective occupational health and safety management. Despite having various sectoral legislative frameworks, there is a notable absence of a comprehensive legal framework specifically addressing chemical safety management issues. Moreover, the existing regulations have not successfully established a nexus between chemical safety, employee well-being, potential opportunities, and task performance. This highlights the insufficient attention given to occupational health and chemical safety issues at the policy level, with limited research dedicated to these critical concerns. Consequently, this critical review aims to identify optimal strategies for the long-term sustainable development of Bangladesh in the realm of occupational chemical safety and management. The review critically evaluates the current state of Bangladesh's national chemical management, offering a policy trajectory for consideration. It meticulously analyzes the disjunctions and incongruities between prescribed guidelines and actual practices in chemical management within the Bangladeshi context. Furthermore, it establishes a comprehensive framework for a nationwide chemical management system, aligning with global best practices and guidelines. The study also delineates existing gaps and challenges while outlining future priorities that warrant immediate government attention and sustained commitment to enhance chemical safety management. Therefore, this study serves as a foundational reference for policymakers not only in Bangladesh but also for those in other developing economies grappling with escalating chemical demands, providing guidance for constructing an appropriate infrastructure and legal framework for enduring chemical management.